2012
DOI: 10.1161/hypertensionaha.111.186593
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response to Controlled Diesel Exhaust Exposure in Human Subjects

Abstract: Exposure to traffic-related air pollution is associated with risk of cardiovascular disease and mortality. We examined whether exposure to diesel exhaust increased blood pressure in human subjects. We analyzed data from 45 nonsmoking subjects, age 18–49 in double-blinded, crossover exposure studies, randomized to order. Each subject was exposed to diesel exhaust, maintained at 200 μg/m3 of fine particulate matter, and filtered air for 120 minutes on days separated by at least two weeks. We measured blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 21 publications
7
83
4
4
Order By: Relevance
“…Assessed as an overall effect, this change in brachial artery caliber is similar to that observed in a previous study by our group (7), which found an average 0.11-mm decrease in BAd 30 minutes after exposure to DE at 200 mg/m 3 . This finding adds to the growing body of literature confirming that acute exposure to traffic-related air pollutants has a consistent and measurable effect on vasocontractility (7,(14)(15)(16)(17)(18) associated with a simultaneous rise in systemic blood pressure (9,19). Interestingly, in this study, we found evidence that both genetic variations and AO supplementation may alter individual susceptibility to the DE exposure.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Assessed as an overall effect, this change in brachial artery caliber is similar to that observed in a previous study by our group (7), which found an average 0.11-mm decrease in BAd 30 minutes after exposure to DE at 200 mg/m 3 . This finding adds to the growing body of literature confirming that acute exposure to traffic-related air pollutants has a consistent and measurable effect on vasocontractility (7,(14)(15)(16)(17)(18) associated with a simultaneous rise in systemic blood pressure (9,19). Interestingly, in this study, we found evidence that both genetic variations and AO supplementation may alter individual susceptibility to the DE exposure.…”
Section: Discussionsupporting
confidence: 75%
“…Some of the results of this study have been previously reported in the form of an abstract (8). Cosselman and colleagues previously published that DE exposure was associated with a rise in systemic blood pressure using data from this experiment combined with two additional studies using our exposure chamber (9).…”
mentioning
confidence: 92%
“…However, consistent with our findings, several studies measuring the association between exposure to environmental pollutants (other than SHS) and BP have reported increases in the systolic BP, with no similar increase in the diastolic BP. 28,29 In addition, systolic BP has recently been shown to be more important than the diastolic BP in estimating the risk of CVD. 28 This study has numerous strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent controlled human inhalation study reported that exposure to diesel exhaust was associated with a rapid and measureable increase in SBP but not DBP. 15 Furthermore, some authors even reported that there was a small significant decrease in DBP and SBP and hypertension in association with particulate air pollution. 16 The reasons for inconsistent effects of ambient air…”
mentioning
confidence: 99%